2013
DOI: 10.1213/ane.0b013e318284123e
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lipid Emulsion on Pharmacokinetics and Tissue Distribution of Bupivacaine in Rats

Abstract: The lipid sink phenomenon was observed in this study. The use of a lipid emulsion accelerated the elimination of bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 23 publications
3
57
1
Order By: Relevance
“…The median individual increase per patient in GCS was 2 points. This effect is consistent with animal models demonstrating decreased brain drug levels when ILE is administered after initial drug distribution [28,29]. While promising, these observations do not hold direct clinical utility.…”
Section: Discussionsupporting
confidence: 74%
“…The median individual increase per patient in GCS was 2 points. This effect is consistent with animal models demonstrating decreased brain drug levels when ILE is administered after initial drug distribution [28,29]. While promising, these observations do not hold direct clinical utility.…”
Section: Discussionsupporting
confidence: 74%
“…Shi et al 11 have shown decreased target organ bupivacaine concentrations, in addition to increased hepatic bupivacaine concentrations following ILE infusion in intact rats. Measured elimination half-life decreased and clearance rate increased, consistent with the forwarded hypothesis of augmented redistribution.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid emulsion also substantially reduced methemoglobin production caused by the three most lipid soluble drugs tested, but not by the other less lipid soluble ones in vitro [19]. Recently, enhanced decrease of the concentration of bupivacaine in multiple organs including the brain and heart by lipid emulsion was shown in rats and in a physiologically based pharmacokinetic model [13,20]. Taken together, these studies support the role of partitioning in lipid resuscitation in treating bupivacaine toxicity and overdose of other lipophilic drugs.…”
Section: Mechanismmentioning
confidence: 58%
“…The primary objective of these animal studies was to elucidate the mechanisms of reversal of the toxic effects of local anesthetics, apart from merely examining the effect of lipid emulsion on their toxicity [11][12][13][14][15]. Two distinct effects, partitioning and enhanced metabolism, have been suggested as possible mechanisms of the antidote effect of lipid emulsion, although the effects are complicated and cannot be explained simply [8].…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation